Efektivitas Model Pembelajaran Make a Match Berbantu Puzzle Matematika untuk Meningkatkan Kemampuan Representasi Matematis - Fida Antika; Sofwan Hadi (Indonesian Mathematics Education Journal, 2024)
The ability of mathematical representation is important in learning Mathematics which is used to build concepts and think mathematically, in problem solving. This study aims to find out (1) the implementation of the learning model on the ability of mathematical representation, (2) the use of the effective learning model on the ability of mathematical representation of students, (3) the ability of mathematical representation of students, 4) the factors that affect the ability of mathematical representation of students. This study uses a quantitative approach with a quasi-experimental type of research. The results were obtained that (1) student activities during the learning activities of the experimental class obtained a score of 87.5% and the control class obtained a score of 71.89%, indicating that students who use the Make A Match model assisted by Puzzle media can play an active role in learning activities. (2) The Make A Match learning model assisted by Puzzle media is quite effective in improving students' mathematical representation skills. This is evidenced by the results of the T test which shows a value of 0.000, and the results of the N-Gain test which shows a score of 0.62 in the category is quite effective. (3) The use of the Make A Match learning model assisted by mathematical puzzle media is very effective in improving visual representation skills, and is quite effective in improving symbolic and verbal representation skills. (4) factors that can affect students' mathematical representation ability are internal factors, namely students' interests, learning styles and student intelligence, and external factors are teachers who lack the use of learning models, and motivation.